AL-IJARAH AL-MUTANAQISHAH: AKAD ALTERNATIVE UNTUK PEMBERDAYAAN TANAH WAKAF - Ridwan, Murtadho (EQUILIBRIUM, 2015)
Empowerment is an attempt to bring the results or even greater and better benefits by using the potentials of someone who have the power. The empowerment of the waqf land aims at developing and producing the waqf land in an effort to get the results and benefits of waqf land itself in general accordance with the provisions that have been required Wakif. This article is a literature review that aims to seek alternative contract in empowering waqf land. The results showed that many literature of jurisprudence have set a contract that can be used to empower waqf land. Among the contract is categorized Ijarah contract in the empowerment of traditional endowment. Therefore, if the economic system is more advanced, the Ijarah develop and innovate so that it appears the contract called IMBT (Ijarah Muntahiyah bi Tamlik). In addition there are al-Ijarah contract al-Mutanaqishah that is very suitable for the empowerment of waqf land. The last contract helped Nazhir in capital for the empowerment of waqf land. This is because all the empowerment of waqf land costs will be paid by investors and after the contract is completed, the financiers will transfer ownership of the building to Nazhir. Pemberdayaan adalah suatu usaha untuk mendatangkan hasil atau manfaat yang lebih besar dan lebih baik dengan memanfaatkan potensi yang dimiliki. Pemberdayaan tanah wakaf bertujuan mengembangkan dan memproduktifkan tanah wakaf sebagai upaya mendapatkan hasil dan manfaat tanah wakaf secara umum  sesuai  dengan  ketentuan  yang  telah  disyaratkan  Wakif. Artikel ini merupakan kajian pustaka yang bertujuan untuk mencari akad alternative dalam memberdayakan tanah wakaf. hasil kajian menunjukkan bahwa banyak literatur fikih yang sudah menentukan akad-akad yang bisa digunakan untuk memberdayakan tanah wakaf. Di antara akad tersebut adalah Ijarah yang dikategorikan akad tradisional dalam pemberdayaan wakaf. oleh karena system perekonomian yang sudah semakin maju, maka akad Ijarah mengalami pengembangan dan inovasi sehingga muncul akad yang disebut dengan IMBT (Ijarah Muntahiyah bi Tamlik). Selain itu ada akad al-Ijarah al-Mutanaqishah yang sangat cocok untuk pemberdayaan tanah wakaf. Akad yang terakhir ini banyak membantu Nazhir dalam permodalan untuk pemberdayaan tanah wakaf. Ini karena semua biaya pemberdayaan tanah wakaf akan ditanggung oleh pemodal dan setelah akad selesai pemodal akan mengalihkan pemilikan bangunan kepada Nazhir.